Focused on multi viewed virtual reality short film ’sweeney TODD - the story of a barber’ production study - Yi. Jung, Hyun; Gi. Kim, Hyung; Hong, Sungdae (International Journal of Engineering and Technology, 2018)
Background/Objectives: The Virtual Reality realistic image content is a technology to enable building imaginary space by synthesizing both real and graphic images so as to provide the sensation of immersion without the distinction between real and virtual world. In addition, this is a realm with strong growth potential requiring the raise of technological maturity in the medium to longer term.Methods/Statistical analysis: This research is an attempt to study the time and structure to acquire multi-view components beyond the degree of simple technological experience of delivering the already constructed information unilaterally. In addition, the direction to selectively solve the key problems in VR image grammar is explored by considering the pipeline of production technology including time control, etc.Findings: In this study, we have examined the necessary element for production such as the actorâ€™s movement, lighting, space set for postproduction stitching and issues that arise in direction by actually producing the VR 360 image in real life. We realized that in the view point of VR 360 image, more than the camera angles, the mise-en-scene and space coordination according to the actorâ€™s movement is more important.Improvements/Applications: VR visual grammarâ€™s liberal point of view has the potential to become a specialized genre where it can extend as a new genre by breaking free from the square frame and specialized formatÂ Â